Hepatocellular carcinoma downstaging for liver transplantation in the era of systemic combined therapy with anti‐VEGF/TKI and immunotherapy. Issue 4 (30th July 2022) - Tran, Nguyen H.; Muñoz, Sergio; Thompson, Scott; Hallemeier, Christopher L.; Bruix, Jordi
Abstract: Hepatocellular carcinoma remains a global health challenge affecting close to 1 million cases yearly. Liver transplantation provides the best long‐term outcomes for those meeting strict criteria. Efforts have been made to expand these criteria, whereas others have attempted downstaging approaches. Although locoregional approaches to downstaging are appealing and have demonstrated efficacy, limitations and challenges exists including poor imaging modality to assess response and appropriate endpoints along the process. Recent advances in systemic treatments including immune checkpoint inhibitors alone or in combination with tyrosine kinase inhibitors have prompted the discussion regarding their role for downstaging disease prior to transplantation. Here, we provide a review of prior locoregional approaches for downstaging, new systemic agents and their role for downstaging, and finally, key and critical considerations of the assessment, endpoints, and optimal designs in clinical trials to address this key question. Abstract : Criteria for downstaging.